NADPH oxidase NOX2 mediates TLR2/ 6‐dependent release of GM‐CSF from endothelial cells. Issue 6 (8th March 2017) - Schuett, Jutta; Schuett, Harald; Oberoi, Raghav; Koch, Ann‐Kathrin; Pretzer, Silke; Luchtefeld, Maren; Schieffer, Bernhard; Grote, Karsten
ABSTRACT: NADPH oxidase–generated reactive oxygen species (ROS) from immune cells are well known to be important for pathogen killing in response to TLR ligands. Here, we investigated a new aspect of NADPH oxidase in the TLR2/6‐induced release of the immunologically relevant GM‐CSF by endothelial cells. Stimulation of human endothelial cells with TLR2/6 agonist, MALP‐2 (macrophage‐activating lipopeptide of 2 kDa), induced NADPH oxidase activation and ROS formation. Inhibition by ROS scavengers and NADPH oxidase inhibitors blocked MALP‐2–induced GM‐CSF release. NADPH oxidase activators or ROS donors alone did not result in GM‐CSF secretion; however, additional superoxide supply augmented MALP‐2–induced GM‐CSF secretion and restored GM‐CSF levels after NADPH oxidase inhibition. MALP‐2–dependent NF‐ĸB activation was suppressed by NADPH oxidase inhibition, and inhibition of NF‐ΚB completely blunted MALP‐2–induced GM‐CSF release. Vascular explants from mice that were deficient for the NADPH oxidase subunit p47 phox showed diminished intimal superoxide production and GM‐CSF release after ex vivo stimulation with MALP‐2. Moreover, an increase in circulating progenitor cells after MALP‐2 injection was completely abolished in p47 phox ‐knockout mice. Finally, MALP‐2 stimulation increased mRNA expression of the major subunit NADPH oxidase, (Nox)2, in endothelial cells, and Nox2 inhibition prevented MALP‐2–induced GM‐CSF release. Our findings identify a Nox2‐containing NADPH oxidase as a crucial regulator of the immunologic important growth factor GM‐CSF after TLR2/6 stimulation in endothelial cells.—Schuett, J., Schuett, H., Oberoi, R., Koch, A.‐K., Pretzer, S., Luchtefeld, M., Schieffer, B., Grote, K. NADPH oxidase NOX2 mediates TLR2/ 6‐dependent release of GM‐CSF from endothelial cells. FASEB J. 31, 2612–2624 (2017). www.fasebj.org